Effective School Management Strategies for Enhancing Early Childhood Development - Subhan Subhan; Shobihatul Fitroh Noviyanti; Ihsan Zikri Ulfiandi; Musammil Lateh (Education and Sociedad Journal, 2024)
This article examines effective school management strategies in developing early childhood skills at early childhood education.  The purpose of this research is to explore the interplay between strategic management practices, collaborative decision-making, and parent and community engagement in fostering the holistic development of young learners. Utilizing a descriptive qualitative research method, data were collected through interviews, observations, and documentation, and analyzed using triangulation techniques to ensure reliability and validity. The findings reveal that collaborative decision-making and innovative school management strategies, such as natural learning and digital learning approaches, play crucial roles in promoting early childhood skills development. Moreover, the study underscores the significance of parent and community engagement initiatives, including parenting programs, student guardian associations, and home visits, in creating supportive ecosystems where children can thrive academically, socially, and emotionally. This research highlights the importance of strategic school management practices and proactive engagement with parents and the community in nurturing the comprehensive development of young learners in early childhood education settings.